2019
DOI: 10.1093/rheumatology/kez220
|View full text |Cite
|
Sign up to set email alerts
|

Association of systemic lupus erythematosus (SLE) genetic susceptibility loci with lupus nephritis in childhood-onset and adult-onset SLE

Abstract: Objective LN is one of the most common and severe manifestations of SLE. Our aim was to test the association of SLE risk loci with LN risk in childhood-onset SLE (cSLE) and adult-onset SLE (aSLE). Methods Two Toronto-based tertiary care SLE cohorts included cSLE (diagnosed <18 years) and aSLE patients (diagnosed ⩾18 years). Patients met ACR and/or SLICC SLE criteria and were genotyped on the Illumina Multi-Ethnic Globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 37 publications
4
25
0
Order By: Relevance
“…Genetic risk scores (GRSs) have been applied in several fields of medicine, and studies have demonstrated their ability to predict matters like cardiovascular disease, prostate cancer risk and body mass index scores 22–24. In SLE, few studies have assessed the relationship between the cumulative genetic risk and disease subphenotypes,25–28 and the association between the polygenic risk and disease severity is unknown. In this study, we examined the relationship between a high GRS and clinical manifestations associated with more severe SLE phenotypes, including organ damage, defined by the Systemic Lupus Collaborating Clinics (SLICC)/American College of Rheumatology (ACR) Damage Index (SDI),29 cardiovascular events (CVE) and end-stage renal disease (ESRD).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic risk scores (GRSs) have been applied in several fields of medicine, and studies have demonstrated their ability to predict matters like cardiovascular disease, prostate cancer risk and body mass index scores 22–24. In SLE, few studies have assessed the relationship between the cumulative genetic risk and disease subphenotypes,25–28 and the association between the polygenic risk and disease severity is unknown. In this study, we examined the relationship between a high GRS and clinical manifestations associated with more severe SLE phenotypes, including organ damage, defined by the Systemic Lupus Collaborating Clinics (SLICC)/American College of Rheumatology (ACR) Damage Index (SDI),29 cardiovascular events (CVE) and end-stage renal disease (ESRD).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, women are more predisposed to SLE than men, and the disease prevalence ratio of women is about 9:1 over men 2 . Autoantibody production and gender bias in SLE is caused by a combination of genetic and environmental factors [1][2][3][4] . Disproportionate functioning of genes as well as sex hormones, estrogen in particular, contribute to the onset and development of disease activities in SLE 2,[5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE), an autoimmune disease, arises when abnormally functioning B lymphocytes produce auto-antibodies to DNA and nuclear proteins, resulting in immune complexes that cause damage to the tissue [1]. While the triggers are not known, it is generally believed that SLE is caused by a combination of genetic and environmental factors [1][2][3]. Dietary factors can also have a profound impact on the gut and systemic immune responses [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%